PENGARUH STORE ATMOSPHERE, BRAND IMAGE, VARIETY PRODUCT TERHADAP KEPUASAN KONSUMEN (SURVEI PADA KONSUMEN WARUNK WOW KWB PONOROGO) - Vivi Dwi Pebriyanti; Naning Krisiyana; Premi Wahyu Widyanigrum (Jurnal Manajemen, 2022)
This study aims to determine the effect of Store Atmosphere, Brand Image, Product Variety on Consumer Satisfaction (Survey on Consumers of Warunk WOW KWB Ponorogo). The sample in this study was 100 respondents who met the criteria determined by the researcher. The testing phase used includes instrument testing, coefficient of determination test and hypothesis testing and classical assumption testing. The analysis used in this research is multiple linear regression analysis. The results of this study indicate that: (1) Store Atmosphere partially has a significant effect on Consumer Satisfaction, (2) Brand Image partially has a significant effect on Consumer Satisfaction, (3) Variety Product partially has a significant effect on Consumer Satisfaction.